Underground 3D utility mapping: comparison assessment between ReflexW and Revit / Muhammad Haziq Zahiruddin Hanafi - Hanafi, Muhammad Haziq Zahiruddin (2023)
Mapping utilities in three dimensions is essential for ensuring efficient urban development and protecting utility infrastructure in automated construction projects. Nonetheless, the ever-expanding urban areas, cities with limited land resources, and unknown subterranean spaces present significant obstacles to utility mapping and management. For instance, locating and identifying underground utility conduits is one of the most persistent challenges due to the presence of various mediums such as gas, water, oil, and others, making it particularly difficult to determine the diameter of these conduits. In addition, historic urban areas frequently have inadequately documented or ambiguous underground pipeline configurations, making accurate mapping even more difficult. The archival management of subsurface pipeline facilities is unorthodox and insufficiently documented. This study aims to compare the efficacy of 2D and 3D Ground Penetrating Radar (GPR) data visualization using ReflexW and Autodesk Revit. Using these cutting-edge technologies, the study seeks to evaluate the precision and dependability of 3D visualization capabilities in utility mapping. The data collection procedure in the Tok Arau Complex consists of several phases, including surveillance, GPR and PCL calibrations, and GPS-based RTK Network comprehensive surveying. The culmination of these efforts is the compilation of an exhaustive 3D model that facilitates a visual representation of the underground utility infrastructure. Additionally, the study employed the Root Mean Square Error (RMSE) as a metric to evaluate the veracity of the software's 3D visualization capabilities. The RMSE value, with a precision of 0.05, indicates that Revit software can be used to construct underground pipelines.